THE INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND INFRASTRUCTURE ON TEACHERS' PROFESSIONAL COMPETENCIES IMPLEMENTING THE CURRICULUM INDEPENDENCE AT VOCATIONAL SCHOOL STATE 1 FUCK SEI TUAN - Erni, Netti; Pratiwi, Sri Nurabdiah; Amiruddin, Amiruddin (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This research aims to determine the influence of the principal's leadership, organizational culture, and infrastructure on the professional competence of teachers at SMK Negeri 1 Percut Sei Tuan. This research is ex-post facto research using quantitative methods. The population was 150 people and the sample was 109 people. Based on the results of the hypothesis testing analysis that has been carried out, the significance value (Sig) of the principal's leadership variable (X1) is the result of the calculation, namely a = 3.478 and b = 0857. So a simple linear regression equation is obtained for hypothesis 1, namely: Ŷ = 3.478 + 0.857X1 . Based on data, the regression coefficient value for school principal leadership is 0.857. Second hypothesis. The calculation results obtained are a = 36,964 and b = 1,618. By entering the prices a and b into the regression equation, a simple linear regression equation is obtained for hypothesis 1, namely: Ŷ = 36,964 + 1,618 X2. Based on data, the organizational culture regression coefficient value is 1,618. The third hypothesis resulting from the calculation is a = 5,780 and b = 1,194. By entering the prices a and b into the regression equation, a simple linear regression equation is obtained for hypothesis 1, namely: Ŷ = 5,780 + 1,194 X2. Based on data, the regression coefficient value for infrastructure is 1,194. The fourth hypothesis calculation results are a = 44.398, b = 0.325, c = 1.192, and d = 0.248. By entering the prices a, b, c, and d into the regression equation, we obtain a multiple linear regression equation for hypothesis 4, namely: Ŷ = 44,398+ 0. 325X1 + 1,192X2 + 0. 248 X3. Based on data, the regression coefficient value for principal leadership is 0.325, organizational culture is 1.192.Keywords:Principal Leadership, Organizational Culture, Infrastructure, Teacher Professional Competence.